2013
DOI: 10.1364/ol.38.002437
|View full text |Cite
|
Sign up to set email alerts
|

Distributed fiber strain and vibration sensor based on Brillouin optical time-domain reflectometry and polarization optical time-domain reflectometry

Abstract: A distributed fiber strain and vibration sensor which effectively combines Brillouin optical time-domain reflectometry and polarization optical time-domain reflectometry is proposed. Two reference beams with orthogonal polarization states are, respectively, used to perform the measurement. By using the signal obtained from either reference beam, the vibration of fiber can be measured from the polarization effect. After combining the signals obtained by both reference beams, the strain can be measured from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…31 Due to these limitations, BOTDR-based dynamic strain sensors have limited frequency range. Wang et al 32 demonstrated such a system with a maximum detectable frequency of 11 Hz over 4 km of sensing fibre. However, the proposed setup had a poor strain sensitivity of 100 µε with a spatial resolution of 10 m.…”
Section: A Brillouin Optical Time Domain Reflectometry (Botdr)mentioning
confidence: 99%
“…31 Due to these limitations, BOTDR-based dynamic strain sensors have limited frequency range. Wang et al 32 demonstrated such a system with a maximum detectable frequency of 11 Hz over 4 km of sensing fibre. However, the proposed setup had a poor strain sensitivity of 100 µε with a spatial resolution of 10 m.…”
Section: A Brillouin Optical Time Domain Reflectometry (Botdr)mentioning
confidence: 99%
“…Then the stress of fiber is determined using Eq. (4) and (5). Apparently, the vibration can be continuously detected at each frequency shift.…”
Section: Methodsmentioning
confidence: 99%
“…Many kinds of distributed optical fiber sensors (DOFS) have been developed for the monitoring of structural health and have gotten satisfying results [1][2][3][4][5][6]. However, only a few of them can monitor both the vibration and strain/temperature simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a novel kind of POTDR intrusion sensor with simple detection algorithm, which was based on the sliding standard deviation of the difference between two consecutive POTDR traces, was demonstrated [ 113 ]. Experimental results showed that an intrusion leading to a 1.5-cm fiber displacement could be detected, with an error on the intrusion localization of 5 m over a total fiber length of 472.5 m. Later, a distributed fiber strain and vibration sensor that effectively combined Brillouin OTDR and POTDR was proposed, a 10-m SR was realized over a 4-km sensing distance [ 114 ]. Afterwards, by using 2nd-order Raman amplification, a long-distance (106 km) POTDR fiber fence system was demonstrated [ 115 ].…”
Section: Distributed Fiber-optic Vibration Sensing Technologymentioning
confidence: 99%